Cerebral NIRS patterns in late preterm and very preterm infants becoming late preterm. (3rd April 2019) - Grometto, Alice; Pizzo, Benedetta; Strozzi, Maria Chiara; Gazzolo, Francesca; Gazzolo, Diego
Abstract: Background: Near Infrared Spectroscopy (NIRS) has been proposed as a useful, noninvasive monitoring technique providing reliable information about central nervous system (CNS) oximetry and function. Recently, brain damage has been reconsidered as a dynamic process evolving over the weeks of gestation. We therefore investigated NIRS cerebral pattern differences between healthy late preterm infants (LPTo) and very preterm infants becoming late preterm (LPT). Methods: We conducted an observational study in 40 healthy late preterm infants, matched for gestational age at monitoring, of whom 20 where LPTo and 20 LPT. Clinical, diagnostic and laboratory monitoring procedures and cerebral oximetry (crSO2 ) and function (cFTOE) were recorded on admission into the study. Results: No significant differences ( p > .05, for all) were found between groups regarding clinical, diagnostic or laboratory parameters. Higher crSO2 and lower cFTOE ( p < .001, for both) were found in the LPTo group. Conclusions: Our results, showing impaired oximetry and function of CNS in LPT, offer additional support to NIRS parameters as a useful tool for longitudinal CNS monitoring of very preterm infants becoming LPT. Future studies correlating NIRS variables and long-term neurological outcome in LPT are needed to elucidate the concept of dynamic brain damage pathogenesis.